Difference of PV Solar Farm Performance between Simulated Result with Actual MÂ¬easurement under Climate Condition at Eastern Peninsular Malaysia - Zulkifli, Siti Farhanah; Abdul Rahman, Hasimah; Yusri Hassan, Mohammad (Journal of Science and Technology, 2017)
Estimation from simulation tool in feasibility study could be rarely achieved under real operating condition since it calculates the expected output power using algorithms embedded in the tools and synthetic solar irradiance data without considering environmental conditions at the actual site. The aim of this study is to identify the differences in performance between measured data and estimated values using HOMER and PVSyst and to develop a baseline system performance prior installation. A case study at the eastern part of Peninsular Malaysia was conducted to examine the effect of climate condition on the performance of PV solar farm. Findings indicated that PV solar farm in Terengganu has generated 5,416,252.49kWh of energy in a year while the annual energy estimated by HOMER and PVSyst are 7,124,650.00kWh and 6,408,925.69kWh, respectively. This shows that the actual energy production is 15% and 24% lower than PVSyst and HOMER. Hence, baseline developed for PV solar farm at eastern region would comprise energy yield from 1,083.25kWh/kWp to 1,281.79kWh/kWp with 12% to 15% capacity factor and performance ratio from 73% to 78% in average. This baseline is useful for PV system integrator as a guideline and reference to estimate the PV system performance prior actual installation.